BARRERAS PARA LA ELECCIÓN DE UN MÉTODO ANTICONCEPTIVO EN PUÉRPERAS DEL HOSPITAL REGIONAL DE ICA EN EL AÑO 2019 - SALAZAR QUISPE, TELMA BELLY (2020)
A woman's ability to initiate a successful, continuous, and appropriate method of contraception is influenced by many different factors; eg access to health care, community, cultural attitudes and personal attitude can be seen as obstacles to applying the correct use and effective method of women to family planning goals. Beekle in a study on awareness and determinants of family planning practice showed that knowledge and access to services alone could not be adequate for the acceptance of contraceptive devices. Furthermore, in developing countries, where women depend on ancient traditions and social limitations, knowledge and awareness about the acceptance of family planning would not be the only deciding factor, as well as the reduction of the reproductive rate7. A study in the United States showed that there are a number of factors complicating the lack of or ineffective use of contraceptive methods among Hispanic women. While economic factors and access to health care are important factors, cultural knowledge, attitude, and values have been shown to impact reproductive behavior. Ozgoli et al also in their study showed that vasectomy advocates begin sterilization with little awareness and positive results. attitude and eligible individuals did not experience it with neutral attitude. Furthermore, in a study in Peru, the non-continuous and unstable causes of condom use mentioned as factors such as different vain beliefs reduce sexual pleasure, bad experiences, fear and anxiety. During sex and society's negative attitude towards condom users. The tendency to use a contraceptive method, as well as any other desire, depends on the general attitude of the individual towards the use of that method. Knowing the attitudes of individuals can be of great importance. By being aware of people's attitudes, their behavior would be predicted and controlled, and as we all know, predicting and controlling behaviors is of great importance to many people as community health professionals.